Kajian Yuridis Pengesahan Perkawinan di Pengadilan Agama Jember (Studi Kasus Putusan Pengadilan Agama Jember Tentang Pengesahan Perkawinan di Bawah Tangan) - Imam Bukhori (STAIFAS-Press, 2016)
Marriage can be said to be valid if done according to Islamic law and in accordance Law - Marriage Law and the Compilation of Islamic Law. Indonesian legal system does not recognize the term under the hand mating, marriage Sirri and the like, and do not set out specifically in a regulation. For those who do not register marriages considered invalid in the eyes of the law and did not get a marriage certificate as proof of the validity of a marriage is authentic. But in the Compilation of Islamic Law article 7 paragraph (2) states: